Analysis of the asset replacement level with an uncertain salvage value : a two-factor model - Zambujal-Oliveira, João (2022)
The aim of this article is to analyse the asset replacement problem from the perspective of optimal replacement level, given a specific tax environment and depreciation policy. Using a real options approach, our model minimizes current operation and maintenance costs and allows the definition of a new value of the replacement flexibility within a multi-cycle environment. The innovation on the valuation process comes from adding an autonomous salvage value’s factor. The results from partial differential equations reveal relevant differences from those observed in one-factor models, especially with regard to optimal replacement levels and in the non-monotonous effects of salvage value variation. The numerical case study also confirms that the salvage value is indeed a worthwhile element in the replacement process. It was possible to determine that, in terms of the magnitude of the cost replacement level, the key roles are played by changes in the speed of mean reversion, as well in the salvage factor volatility. This paper provides some improvements to the existing literature in equivalent annual cost by drawing up a cost minimization problem conditioned by a different salvage value dynamics, and contributes to real options literature by introducing a salvage value factor in the pricing model.